Analysis of pregnancy outcomes in patients with recurrent implantation failure complicated with chronic endometritis - Li, Jie; Li, Xueyao; Ding, Jinli; Zhao, Jing; Chen, Jiao; Guan, Feng; Deng, Haiyu; Zhou, Mengqi; Han, Yiling; Xiao, Zhuoni; Yang, Jing (Frontiers in Cell and Developmental Biology, 2023)
Chronic endometritis (CE) has been considered to reduce uterine receptivity and negatively affect reproductive outcomes for in vitro fertilization-embryo transfer (IVF-ET) patients, especially for people undergoing recurrent implantation failure (RIF). To investigate the effects of antibiotic and platelet-rich plasma (PRP) therapy on pregnancy outcomes following frozen-thawed embryo transfer (FET) in RIF patients with CE, endometrial specimens of 327 patients with RIF obtained by endometrial scratching during mid-luteal phase were immunostained by multiple myeloma oncogene-1 (Mum-1)/syndecan-1 (CD138). RIF patients with CE were given antibiotics and PRP treatment. According to the Mum-1+/CD138+ plasmacytes after treatment, patients were divided into persistent weak positive CE (+) group, CE (−) group and non-CE group. FET was performed and the basic characteristics and pregnancy outcomes of patients in three groups were compared. Among 327 RIF patients, 117 patients were complicated with CE, the prevalence was 35.78%. The prevalence of strong positive was 27.22% and that of weak positive was 8.56%. 70.94% patients with CE converted to negative after treatment. There was no significant difference in the basic characteristics, including age, BMI, AMH, AFC, infertility years, infertility types, number of previous transplant cycles, endometrial thickness on transplantation day and number of transplanted embryos (p > 0.05); The positive rate of hCG, clinical pregnancy rate and implantation rate in CE (−) group were significantly increased compared with the weak CE (+) group and non-CE group (p < .01), and the live birth rate also improved (p < .05). Whereas, the rate of early abortion in CE (−) group was 12.70%, which was higher than that in weak CE (+) group and non-CE group (p < .05). After multivariate analysis, number of previous failed cycles and CE remained independent factors associated with live birth rate, while only CE remained to be the independent factor of clinical pregnancy rate. It is recommended to perform CE-related examination for patients with RIF. Antibiotic and PRP treatment can significantly improve pregnancy outcomes of patients with CE negative conversion in FET cycle.